A case of delayed allergy after cyanoacrylate closure of varicose veins, diagnosed by drug-induced lymphocyte stimulation test - Hiroyuki Suzuki; Mayuko Nakayama; Go Kuwahara; Hideichi Wada (International Journal of Vasculitis, 2023)
Objectives The number of cases of cyanoacrylate closure (CAC) system for varicose veins has been increasing worldwide. However, as this is a new treatment method, the potential adverse effects and other details remain unclear. In particular, the cause of inflammation in embolized veins is still under debate. Methods We performed a drug-induced lymphocyte stimulation test (DLST) on a patient with allergic-like symptoms after CAC. Results The DLST was strongly positive in this case, and the patient underwent total removal of the CAC-filled vein due to difficulty controlling the symptoms with medication. After that the state was recovered and no medication was continued. Conclusion We encountered a case that a delayed allergy by CA after CAC treatment developed in, eventually leading to the total removal of the CA-filled vein. It was suggested that with doubting allergic-like symptom after CAC, DLST for CA could show not only the diagnosis of the delayed allergy to CA, but also the later treatment policy with stimulation index (S.I.) in the positive cases.
Keywords: varicose veins